Mathematical software -- ICMS 2020 : 7th International Conference, Braunschweig, Germany, July 13-16, 2020, Proceedings /: 7th International Conference, Braunschweig, Germany, July 13-16, 2020, Proceedings. (2020) - Unknown
No abstract available